Replacing a suite of commercial pectinases with a single enzyme, pectate lyase B, in Saccharomyces cerevisiae fermentations of cull peaches. (1st April 2014) - Edwards, M C; Williams, T; Pattathil, S; Hahn, M G; Doran-Peterson, J
Abstract: Fermentation of pectin-rich biomass with low concentrations of polysaccharides requires some treatment of the pectin, but does not need complete degradation of the polysaccharide to reach maximum ethanol yields. Cull peaches, whole rotten fruits that are not suitable for sale, contain high concentrations of glucose (27.7 % dw) and fructose (29.3 % dw) and low amounts of cellulose (2.8 % dw), hemicellulose (4.5 % dw) and pectin (5.6 % dw). Amounts of commercial saccharification enzymes, cellulase and cellobiase can be significantly decreased and commercial pectinase mixtures can be replaced completely with a single enzyme, pectate lyase (PelB), while maintaining ethanol yields above 90 % of the theoretical maximum. PelB does not completely degrade pectin; it only releases short chain oligogalacturonides. However, the activity of PelB is sufficient for the fermentation process, and its addition to fermentations without commercial pectinase increases ethanol production by ~12 %.